Recent Levels of Technetium-99 in Seawater at the West Coast of Svalbard. (2002) - Gerland, Sebastian; Lind, Bjørn; Dowdall, Mark; Kolstad, Anne Kathrine
Abstract : Seawater from the western coast of Svalbard was sampled in the spring and summer of 2000 to determine levels of technetium-99 ( 99 Tc), a conservative-behaving, manmade radionuclide originating from European nuclear reprocessing plants. This paper deals with the recent levels of this radionuclide in seawater and with the link between an Arctic fjord, Kongsfjorden, and the Western Spitsbergen Current (WSC), investigated using 99 Tc results. By means of the WSC, the 99 Tc radionuclides ultimately reach the eastern Fram Strait west of Spitsbergen (the largest island of the Svalbard archipelago). Results from oceanographic modelling and sea ice observations indicate a direct coupling between Kongsfjorden and the area west of it. The findings in connection with new radionuclide results presented in this paper concur with these assumptions. Furthermore they indicate that the inner part of Kongsfjorden is also well linked to the WSC. Surface seawater from the central part of the WSC, sampled during a cruise with RV Polarstern in the summer of 2000, shows a higher level of 99 Tc than those measured in Kongsfjorden in spring 2000. However, all levels measured in surface water are of the same order of magnitude. Data from sampling of deeper water in the WSC area provide information pertaining to the lateral distribution of 99 Tc. The results, along with additional data from spring 2001, indicate that Kongsfjorden is suitable for monitoring the levels of 99 Tc arriving in the European Arctic and that the sheltered setting of this fjord does not necessarily provide protection against pollution from the open sea.